2023
DOI: 10.3390/ijms24108738
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the Potential of Royal-Jelly-Incorporated Hydrogel Dressings as Innovative Wound Care Materials

Sonia Kudłacik-Kramarczyk,
Marcel Krzan,
Mateusz Jamroży
et al.

Abstract: The development of multifunctional dressing materials with beneficial properties for wound healing has become a recent focus of research. Many studies are being conducted to incorporate active substances into dressings to positively impact wound healing processes. Researchers have investigated various natural additives, including plant extracts and apiproducts such as royal jelly, to enhance the properties of dressings. In this study, polyvinylpyrrolidone (PVP)-based hydrogel dressings modified with royal jell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…In general, it has been shown that RJ and its components promote wound healing at both animal and cellular levels [ 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 ]. Some components of RJ show anti-inflammatory effects (SA, 10-HDA, and 10-HDAA), some components promote proliferation and migration (MRJPs, especially MRJP2, MRJP3, and MRJP7), whereas some components stimulate regenerative activities (royalactin, royalisin, and 10-HDA) [ 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 ].…”
Section: Biological Function Of Royal Jellymentioning
confidence: 99%
“…In general, it has been shown that RJ and its components promote wound healing at both animal and cellular levels [ 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 ]. Some components of RJ show anti-inflammatory effects (SA, 10-HDA, and 10-HDAA), some components promote proliferation and migration (MRJPs, especially MRJP2, MRJP3, and MRJP7), whereas some components stimulate regenerative activities (royalactin, royalisin, and 10-HDA) [ 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 ].…”
Section: Biological Function Of Royal Jellymentioning
confidence: 99%
“…Photo-curable compositions have been extensively used to produce materials for various applications including in regenerative medicine [8,9], in particular, multifunctional hydrogel dressings [9], biomimetic magnetic structures [10], composites with antimicrobial properties provided by the inclusion of quaternary ammonium salts [11], and materials against Staphylococcus aureus [12]. Recent advances have made it possible to design and print dentures, crowns and mouthguards [13][14][15].…”
Section: Introductionmentioning
confidence: 99%